Pelaksanaan Kebijakan Administrasi Kependudukan Bagi Penduduk Rentan : Studi Suku Anak dalam di Bungo : Studi pada Suku Anak dalam di Kabupaten Bungo Provinsi Jambi - Ovie Yanti (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This research describes the Implementation of Population Administration Policies on Administrative Vulnerable Populations (Study on Suku Anak Dalam in Bungo Regency, Jambi Province). Based on the results of the research, it can be concluded that the implementation of population administration in administratively vulnerable populations such as Suku Anak Dalam (SAD) has been implemented by the Bungo District Government through the Bungo District Population and Civil Registration Office, but only a small proportion of SAD residents are recorded and obtain population documents. This is due to the absence of specific regulations governing the data collection and recording of administratively vulnerable populations such as SAD. In addition, the causes of the lack of optimal administration of administratively vulnerable populations such as SAD in Bungo Regency, Jambi Province are limited resources and funds, as well as natural factors due to the distance from the city, a nomadic and closed lifestyle, plus language problems that are difficult to understand. Therefore, in order to achieve Orderly Population Administration specifically for vulnerable populations such as SAD, there needs to be a policy that applies specifically to SAD residents in addition to policies that apply generally in population administration data collection. In addition, the relevant agencies can carry out cross-sectoral cooperation and need to make special plans regarding the financing of data collection and form a Special Officer Unit to carry out data collection of administratively vulnerable populations such as SAD in the Bungo Regency area.